Embryogenesis of the Uropygial Glands in the Laysan Albatross (Phoebastria immutabilis (Rothschild, 1893): Procellariiformes). Issue 8 (13th April 2017) - Rehorek, S.J.; Wu, J.L.; Smith, T.D.; Beeching, S.C.
ABSTRACT: An avian uropygial gland is located on the mid‐dorsum of the tail, and is the only external gland found in birds. Most studies have focused on the function, gross anatomy and chemical nature of this gland, with little research on its ontogeny. The purpose of this study was to examine the development of this gland in a series of Laysan Albatross ( Phoebastria immutabilis ) embryos. Specimens were examined anatomically and histologically. It was found that grooves preceded glandular development by many stages. The embryogenesis of the uropygial gland was divided into 6 phases: preinception, groove inception, mesodermal separation, migrating mesodermal cells, oval shaped "depressions", constriction and finally glandular inception. No other gland is known to develop similarly, though there may be parallels with femoral gland development. In comparison to other bird species, the length of the development period in the Albatross, as well as other compounding factors, make it difficult to determine the significance of these observations. The development of a mesodermal band, soon to be a connective tissue capsule, is more complex than originally described in ducks. Thus, the unique nature of this gland is established, but the significance of the observations required further studies into uropygial gland development. Anat Rec, 300:1420–1428, 2017. © 2017 Wiley Periodicals, Inc.